Prevalence of anxiety and depression symptoms in pregnant women with type 2 diabetes and the impact on glycaemic control. Issue 3 (8th January 2021) - Ásbjörnsdóttir, Björg; Vestgaard, Marianne; Do, Nicoline C.; Ringholm, Lene; Andersen, Lise L. T.; Jensen, Dorte M.; Damm, Peter; Mathiesen, Elisabeth R.
Abstract: Aims: To study the prevalence of anxiety and depression symptoms in pregnant women with type 2 diabetes compared with pregnant women without diabetes. Secondly, to explore whether anxiety and/or depression symptoms in early pregnancy have an impact on glycaemic control and gestational weight gain. Methods: A prospective cohort study of 90 consecutive singleton pregnant women with type 2 diabetes and 88 singleton pregnant women without diabetes. All women completed the Hospital Anxiety and Depression Scale questionnaire in early and late pregnancy. A score ≥8 in the anxiety or the depression scale was used to define anxiety and/or depression symptoms. Results: Anxiety and/or depression symptoms were present in 40% of women with type 2 diabetes and 7% of women without diabetes in early pregnancy (Relative Risk = 5.87 (95% Confidence Interval: 2.60–13.22)). The figures were similar in late pregnancy. In women with type 2 diabetes and anxiety and/or depression symptoms in early pregnancy, HbA1c (mean ± SD) was 52 ± 14 vs. 49 ± 11 mmol/mol (6.9 ± 1.2 vs. 6.6 ± 1.0%), p = 0.31 in early pregnancy and 43 ± 8 vs. 40 ± 4 mmol/mol (6.1 ± 0.7 vs. 5.8 ± 0.4%), p = 0.04 in late pregnancy compared with women without symptoms. Gestational weight gain was similar in both groups. Conclusions: In women with type 2 diabetes, 40% had anxiety and/or depression symptoms in early pregnancy. Women with these symptoms obtained less optimal glycaemic control in late pregnancy but similar gestational weight gain as the remaining women.